(untitled) (The University of Nairobi Journal of Language and Linguistics, 2023)
This paper compares the language policies in education (past and present) in Ethiopia and Kenya. It shows the role played by both international and indigenous languages, e.g. as languages of instruction in education in either country. Multilingualism is reflected in a different way in the education system of either country, as Ethiopia has over eighty languages, while Kenya has about forty-two. An analysis of Strengths, Weaknesses, Opportunities and Threats (i.e. a SWOT analysis) of the language policies in education in the two countries is carried out with a view to showing how each can be improved in their respective multilingual settings. In the specific case of language policies in Kenya and Ethiopia, the aim of a SWOT analysis is to help those concerned with them to think of a language policy in education that may strengthen the position of indigenous languages, so that these can coexist on an almost equal footing with the dominant languages of education. The main strength seen in the language policy in education in Kenya is the introduction of Kiswahili as a compulsory subject both in primary and secondary school. For Ethiopia, a major strength of its current language policy is the promotion of many indigenous languages through education, since some of them are learnt as school subjects. More relevantly, primary school education is conducted in the vernacular. A major weakness of the educational policy in Kenya is that none of the indigenous languages, apart from Kiswahili, is taught as a subject, while in the case of Ethiopia a major weakness is that a solid mastery of English is lacking, yet it is the medium of instruction for secondary and higher education. With regard to opportunities, both countries have an opportunity to develop all languages by having them in written form. In this connection, more elementary books for mother tongue education could be prepared for both big and small languages. In both countries, the only threat to the use of the mother tongue in education is the negative attitude of parents, teachers and students towards it.